The radial distribution of temperature and electrical conductivity in lightning core current-carrying channel and its time evolution - Pin Lyu; Ping Yuan; Wangsheng Wang; Yingying An; Tingting An; Hong Deng; Lizhen Yuan (Atmospheric Research, 2026)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

Electrons of d-orbital (Mn) and p-orbital (N) enhance the photocatalytic degradation of antibiotics by biochar while maintaining biocompatibility: A combined chemical and biological analysis - Jinrui Dong; Pin Li; Xiaoyuan Ji; Yong Kang; Xue Yuan; Jingchun Tang; Boxiong Shen; Huajiang Dong; Honghong Lyu (Journal of Hazardous Materials, 2023)

Load identification of a 2.5 MW wind turbine tower using Kalman filtering techniques and BDS data - Da Wei; Dongsheng Li; Tao Jiang; Pin Lyu; Xiaofei Song (Engineering Structures, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Preparing for real-time weather risk management: the decision models of household evacuation under uncertainty for Taiwanese and US residents - Ya-Pin Lyu; Terri Adams (Natural Hazards, 2022)

A hemizygous mutation in the androgen receptor gene causes different phenotypes of androgen insensitivity syndrome in two siblings by disrupting the nuclear translocation - Chunjie Liu; Yongfen Lyu; Pin Li (Molecular Genetics and Genomics, 2020)

Autonomous cyanobacterial harmful algal blooms monitoring using multirotor UAS - Pin Lyu; Yasir Malang; Hugh H.T. Liu; Jizhou Lai; Jianye Liu; Bin Jiang; Mingzhi Qu; Stephen Anderson; Daniel D. Lefebvre; Yuxiang Wang (International Journal of Remote Sensing, 2017)